การวิเคราะห์ส่วนเก็บไว้ภายใต้ฟังก์ชันการอยู่รอดร่วมสูงสุดระหว่างบริษัทเอาประกันภัยต่อและบริษัทรับประกันภัยต่อ - เจนณรงค์ สถาพรพิบูลย์ (จุฬาลงกรณ์มหาวิทยาลัย, 2014)
The aim of this study is to propose simply method to analyze optimal reinsurance retention for a life insurance plan for ages 50-70 years old which face amount limit is 200,000 baht from one Thai life insurance Company. Optimal retention can be determined by maximizing the joint survival probability provided ceding company and reinsurer do not get loss. Using claim experience from 9,734 policies, this joint survival probability can be estimated by two simple methods including consideration the lower bound of joint survival function and approximation the joint survival function with bivariate translated gamma distribution. As the result of this study, the optimal retentions analyzed with the maximizing lower bound of joint survival function are quota share level 50% for quota share reinsurance with probability as 0.5403 and retention limit 60,000 baht for excess of loss reinsurance with probability as 0.5341. Moreover, the bivariate translated gamma distribution also reveals optimal retentions which quota share level 50% for quota share reinsurance with probability as 0.8388 and retention limit 60,000 baht for excess of loss reinsurance with probability as 0.7331. In conclusion, excess of loss reinsurance with retention limit 60,000 baht is optimal for this life insurance plan.